Influence Factors Nutritional Needs in the Elderly in Marginalized Communities: Pengaruh Faktor yang Mempengaruhi Kebutuhan Status Gizi Lansia di Pulau Kodingareng Kota Makassar - Andi Maryam; Andi Elis; Asni Hasanuddin; Muh Khidri Alwi; Ahmad Syaekhu; Ricvan Dana Nindrea (Jurnal Penelitian Pendidikan IPA, 2023)
Nutritional problems are caused by rapid degradation which causes changes in nutritional status. This study aims to determine the factors that affect the nutritional needs of the elderly on Kodingareng Island in 2023. The research design was carried out in a descriptive-correlative way with a cross-sectional study approach with 49 respondents. The data collection tool is in the form of a questionnaire in the form of a dichotomy. The sample collection technique used is total sampling. The research results show that there is a relationship that influences nutritional needs on the nutritional status of the elderly, namely physical activity, mental condition, depression, disease treatment, and biological decline with a p-value <0.05. The conclusion is obtained that the nutritional status of the elderly is in the normal category, so it is recommended for the community to optimize attention to the food consumed so that they remain at normal nutritional status as well as in administering drugs so that absorption is more optimal.